Traditional, complementary, and integrative medicine in the management of ischemic stroke: a narrative review - Sowmiya, S.; Begum, Rukaiah Fatma; Dhivya, L. S.; Rajendran, Praveen; Harikrishnan, N.; Singh S, Ankul (Frontiers in Pharmacology, 2025)
Ischemic stroke remains a leading cause of mortality and long-term disability worldwide, despite advancements in acute intervention and rehabilitation strategies. Traditional, Complementary, and Integrative Medicine (TCIM) systems; including herbal medicine, acupuncture, and mind-body interventions are increasingly being explored as adjunct therapies in stroke management. This narrative review evaluates the current evidence supporting TCIM approaches for ischemic stroke, highlighting their potential neuroprotective, anti-inflammatory, antioxidant, and cerebrovascular effects. Particular emphasis is placed on well-studied botanical interventions such as Salvia miltiorrhiza Bunge [Lamiaceae; Salviae miltiorrhizae radix et rhizoma], Ginkgo biloba L. [Ginkgoaceae; Ginkgo folium], and Panax ginseng C.A. Mey. [Araliaceae; Ginseng radix]. The review discusses the mechanisms of action, clinical trial outcomes, and integration challenges, while underscoring the need for standardization, quality control, and rigorous scientific validation. This work aims to support informed decisions regarding the integration of evidence-based TCIM practices into conventional stroke care protocols.